Heart transplant outcomes in patients with mechanical circulatory support: cold storage versus normothermic perfusion organ preservation. (22nd November 2020) - Sponga, Sandro; Benedetti, Giovanni; de Manna, Nunzio Davide; Ferrara, Veronica; Vendramin, Igor; Lechiancole, Andrea; Maiani, Massimo; Nalon, Sandro; Nalli, Chiara; Di Nora, Concetta; Bortolotti, Uberto; Livi, Ugolino
Abstract: OBJECTIVES: Patients with mechanical circulatory support bridged to a heart transplant (HTx) are at higher risk of postoperative graft dysfunction. In this subset, a mode of graft preservation that shortens graft ischaemia should be beneficial. METHODS: The outcomes of 38 patients on mechanical circulatory support (extracorporeal life support, left ventricular assist device and biventricular assist device) who received a HTx between 2015 and 2020 were analysed according to the method of graft preservation: cold storage (CS) group, 24 (63%) or ex vivo perfusion (EVP) group, 14 (37%). RESULTS: The median age was 57 (range 30–73) vs 64 (35–75) years ( P  = 0.10); 88% were men ( P  = 0.28); extracorporeal life support was more frequent in the CS group (54% vs 36%; P  = 0.27) versus left ventricular and biventricular assist devices in the EVP group (46% vs 64%; P  = 0.27). Clamping time was shorter in the EVP group ( P  < 0.001) and ischaemic time >4 h was higher in the CS group ( P  = 0.01). Thirty-day mortality was 13% (0–27%) in the CS group and 0% ( P  = 0.28) in the EVP group. A significantly lower primary graft failure [7% (0–23%) vs 42% (20–63%); P  = 0.03] was observed in the EVP group. Survival at 1 year was 79 ± 8% (63–95%) in the CS group and 84 ± 10% (64–104%) in the EVP group ( P  = 0.95). CONCLUSIONS: Our results support the use of ex vivo graft perfusion in patients on mechanical circulatory support as a bridge to a HTx. This technique, by shortening graft ischaemic time, seems to improve post-HTx outcomes. Abstract : The purpose of mechanical circulatory support (MCS) as a bridge to a heart transplant (HTx) is to provide temporary haemodynamic stabilization in patients with advanced cardiac failure, allowing recovery of organ function; therefore, the use of MCS is growing worldwide, given the increasing need for HTx and the global donor shortage [1, 2].